When endometrioma becomes malignant: a clinical case and conclusions for oncogynecological practice - Rybin, Andriy; Liskovskyi, Sergiy (Journal of Education, Health and Sport, 2025)
Objective. To evaluate the clinical and morphological features of malignant transformation of ovarian endometrioma and to emphasise the importance of oncological vigilance in the management of patients with endometriosis. Materials and methods. A clinical case of early endometrioid carcinoma of the ovary against the background of endometrioma in a woman of reproductive age is presented. An analysis of current literature data and ESGO, ESHRE, and JSGO recommendations for the diagnosis and treatment of such patients was performed. Results. Morphological and radiological signs of increased oncological risk were identified, which became the basis for timely surgical intervention. Endometrioid carcinoma G1, FIGO IA was histologically verified. Fertility-preserving staging surgery was performed. No recurrence was detected during 24 months of follow-up. Conclusions. Ovarian endometrioma can be a source of early gynaecological cancer processes even in young patients. Vigilance, high-quality imaging and adequate surgical tactics are key factors for successful treatment.